(3eTcdGJ GdedcjI GdYbGQjI ai GdbGfhf GdadSWjfi (B: s (3OQGSI JMdjdjI h ebGQfI (B/ s - (3eMeO YhV eMeO bfOjds; (3YHOGdgGOj ahRi GdYhVi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B-(3LGeYI GdbGgQI ,s, 2019)
(3HMKJ GdOQGSI eTcdGJ GdedcjI GdYbGQjI ai GdbhGfjf GdadSWjfjI GdSGQjI GdeaYhd ai bWGY ZRI(B: (3YHQ aUdjf GSJYQVJ ajgeG(B: (3dMb GdedcjI h CKQ JTQjYg ai Md eTcdGJ GdedcjI GdYbGQjI(B: (3ef NdGd fXGei GdMjGRI h GdJbGOe(B: (3GddPjf LGA HgeG GdbGfhf GdeOfi GdadSWjfi Qbe (B4 (3dSfI (B2012(3e(B: (3Ke JYQVJ GdOQGSI dMb GdJUQa(B: (3h JfGhdJ eTcdGJg HGYJHGQg Mb eJaQY Yf Mb GdedcjI(B: (3GdPi jedcg GdCaQGO aj GdCQGVi GdCejQjI h CQGVj GdOhdI GdNGUI(B: (3Ke HjfJ fXGe GdTgQ GdYbGQi GdSGQi ai bWGY ZRI(B: (3h hbaJ Ydi eTcdGJg ai GcJSGH edcjI GdYbGQGJ h JSLjdgG(B: (3h GLJgOJ GdOQGSI ai JMOjO GdCQGVi GdJi jLhR MjGRJgG ai bWGY ZRI(B: (3Ke NUUJ GdOQGSI LRkAG efgG dHMK eTcdGJ GdJbGOe GdecSH ai GdbGfhf GdeOfi GdadSWjfi(B: (3h eGgi GdYbGQGJ GdJi JcJSH edcjJgG HGdJbGOe GdecSH(B: (3h CNjkQG GfJgJ Edi NGJeI GSJYQVJ GdfJGFL GdJi JhUdJ EdjgG h GdJhUjGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B264-275s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdeOfjs; (3GdCQGVi GdCejQjIs; (3GdCQGVi ZjQ GdeSLdIs; (3GdedcjI GdYbGQjIs; (3JYQja GdMjGRI s; (3GdMjGRI GdbGfhfjI s; (3GdMjGRI GdYQVjI s; (3GdJbGOe GdecSH s; (3GdTgQ GdYbGQj aj GdbGfhf GdadSWjfj s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs